2012
DOI: 10.1111/j.1524-475x.2011.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual substance P levels after capsaicin treatment correlate with tendon repair

Abstract: The aim of the study was to assess healing after capsaicin-induced substance P (SP) depletion during rat Achilles tendon repair by biomechanical testing. Capsaicin treatment reduced the concentrations of SP by ∼60% and calcitonin gene-related peptide by ∼40% as compared with the control group, as assessed by radioimmunoassay in the dorsal root ganglia, at 1 and 4 weeks post-tendon rupture. Also, the peripheral neuronal presence of SP and calcitonin gene-related peptide, as assessed by immunohistochemistry, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…1). 6,10 Specific sensory denervation results in delayed reepithelialization, as well as hindered tendon wound healing. 6,10,11 Treatment with capsaicin also delays healing of gastric mucosal injuries.…”
Section: Discussion Of Findings and Relevant Literature Neuropathymentioning
confidence: 99%
See 3 more Smart Citations
“…1). 6,10 Specific sensory denervation results in delayed reepithelialization, as well as hindered tendon wound healing. 6,10,11 Treatment with capsaicin also delays healing of gastric mucosal injuries.…”
Section: Discussion Of Findings and Relevant Literature Neuropathymentioning
confidence: 99%
“…1). 10 Thus, capsaicin-mediated denervation is believed to exert its effects mainly via SP-and secondly by CGRPinhibition. Higher residual SP levels in rats treated with capsaicin correlated with better resultant biomechanical tissue properties of the scar tissue, that is, transverse area, ultimate tensile strength and stress at failure.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown that tenocytes have the ability to produce neuro-mediators on their own in tendinopathy [15]. In acute tendon injury or rupture, SP is known to be involved in tissue healing through multiple functions such as inflammatory response, pain transmission, increased vascular permeability and blood flow, and cellular proliferation [6,16,17,18]. However, the actual role of SP among the various neuro-mediators in the pathogenesis of degenerative tendinopathy (e.g., chronic tendon injury) is still being debated.…”
Section: Introductionmentioning
confidence: 99%